LOCUS OF CONTROL, TIME BUDGET PRESSURE DAN PENYIMPANGAN PERILAKU DALAM AUDIT - Nadirsyah Nadirsyah; Intan Maulida Zuhra (Program Magister Akuntansi Unsyiah, 2009)
This research has purpose to show influence locus of control and timebudgetpressure to disfunctional audit behavior. This research is a census research which committed at BPKP Province of Aceh. Population in this research amount 85 auditors. Data using in this research is primary data which obtained through questionare. Data analysis in this research is committed by using multiple linear regression method.The result of this research indicates that partially locus of control has an influence to disfunctional audit behavior. As locus of control, Time budget pressure also has an influence to disfunctional audit behavior. Silmultaneously, it indicates that locus of control and time budget pressure have also an influence to disfunctional audit behavior. Keyword: locus of control, time budget pressure and disfunctional audit behavior